Control of Listeria monocytogenes on Frankfurters by Surface Treatment with Olive Mill Wastewater Polyphenolic Extract - Rossana Roila; Andrea Valiani; Maurizio Servili; David Ranucci; Roberta Galarini; Roberta Ortenzi; Sara Primavilla; Raffaella Branciari (Foods)
Listeria monocytogenes (LM) is a frequent post-process contaminant in meat products. This study aimed to investigate the antilisterial effectiveness of post-process antimicrobial treatments employing olive mill wastewater polyphenolic extract (PE) in commercially manufactured frankfurters. Frankfurters were inoculated on the surface with a three-strain LM mixture (~102 CFU/g), treated on the surface with PE in a 2-fold series of concentrations (PM, 2PM, 4PM) and a control group (CTR) of PE-untreated samples. Then, the frankfurters were vacuum-packed and stored at 4 °C for 28 days. Samples were examined on days 0, 7, 14, 21, and 28 for LM count, in silico growth modeling, and impacts on pH, water activity (aw), and sensory characteristics. From T(time) 7, the PE treatment showed a significant effect on LM growth, registering maximum Δ values between CTR and 4PM of 3.19, 4.86, 4.59, 4.39 at T7, T14, T21, T28, respectively. Minimum effect was attributable to PM treatment with Δ values (CTR versus PM) of 2.07, 2.52, 1.14, 0.65 at T7, T14, T21, T28, respectively. No significant changes occurred in pH (average 6 at T0 and 5.9 at T28), aw (average 0.978 at T0 and 0.968 at T28), nor in sensory profile (p > 0.05). These findings suggest that PE is an effective natural antimicrobial, offering a promising approach to enhancing food safety and extending shelf life in meat products.